An Analysis of Students' Errors in Constructing the Concept of Integer Operations Based on Assimilation and Accommodation - Kurniati, Dian; A’yun, Qurrota; Jatmiko, Dhanar Dwi Hary; Pambudi, Didik Sugeng; Oktavianingtyas, Ervin; Sutarto, Sutarto; Osman, Sharifah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
Errors in constructing concepts often occur in mathematics learning, especially in the topic of integer operations. These errors arise because students tend to memorize procedures or rules without fully understanding the underlying concepts. This research aims to analyze students' errors in constructing the concept of integer operations based on assimilation and accommodation. This study uses a qualitative method with 16 students from class VII B at MTs Baitul Hikmah Tempurejo as subjects. The data collection methods in this study included tests and interviews. Data analysis was carried out through the stages of analyzing test results, conducting interviews, and triangulating the data to ensure validity. Based on the analysis and discussion of the data, it can be concluded that all subjects experienced errors in constructing the concept. Four types of concept construction errors were identified: Pseudo Construction, Construction Hole, Mis-logical Construction, and Mis-analogical Construction. Pseudo Construction occurs when a student merely memorizes phrases like "negative meets negative, the result is positive" without a deeper understanding of the concept. Construction Hole occurs when a student provides incorrect answers due to incomplete understanding or failure to comprehend the problem. Mis-logical Construction happens when a student makes an incorrect assumption or conclusion, while Mis-analogical Construction involves false analogies, such as equating the concept of adding negative numbers with adding positive numbers. The results of this study are expected to provide insights into the types and causes of errors in concept construction made by students, which can then be used as a basis for developing effective learning strategies to help students understand concepts correctly.